Optimization of Body Size and Centroid Position of the Quadruped Robot based on Improved Particle Swarm Optimization Algorithm - Kai Tang; Huanlong Wu; Liang′an Zhang; Ranming Ji; Yongjie Zhao; Xiaoyi Wang; Xinjian Lu (Jixie chuandong)
Taking the quadruped robot as research object， a method to optimize body size and centroid position of the quadruped robot based on improved particle swarm optimization algorithm to enhance its stability is proposed. In order to establish optimization performance evaluation indexes and design variables， the body dynamics model is established， the influence of different centroid positions of the robot on its motion stability is analyzed. Through the analysis， the maximum turning angle minimum is taken as the performance evaluation index， and the body size and centroid position are taken as the optimization design variables. After optimization by improved particle swarm optimization algorithm and ideal point method， a group of optimal body size and centroid positions are obtained. The results show that before optimization， the body can be accelerated and decelerated on the left and right side， its maximum turning angle is 10.10°. After the optimization of the size and the centroid positions， the maximum turning angle is 4.34°， which keeps stable fluctuation in a small range on the same side. Compared with that before optimization， the maximum turning angle of the body is reduced by 5.76°. The experimental prototype of a quadruped robot runs smoothly， validates the effectiveness of the optimization method， and also provides a certain theoretical reference for the stability research of quadruped robot in the future.